Éloi Ficquet, Ahmed Hassen Omer, and Thomas Osmond, eds, Movements in Ethiopia: Ethiopia in Movement. Proceedings of the 18th International Conference of Ethiopian Studies, I–II - Panini, Francesca (Aethiopica, 2017)
Review